A Development of Core Assets Identification System for Software Product Line - Omar, Siti Sarah; Sulaiman, Rabatul Aduni (Applied Information Technology And Computer Science, 2022)
The Software Product Line (SPL) is a collection of features that may be used to efficiently establish the software set in managing feature specific demands for producing common core assets products and reviewing software testing methods. Due to large sizes of products that are continuously being developed, testing is used to manage the core assets variability and commonality using effective ways in SPL. The framework for incorporating core assets into a strategic reuse concept, which includes critical activities such as core asset development, product development, and management in specific practice areas. SPL consists of two processes which are domain engineering and application engineering. Developing proper testing techniques to decrease and eliminate incorrect results with less efforts is critical to having manageable core assets. In software product lines, reusability is widely used to assess respective core assets.